2020
DOI: 10.3390/s20092502
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Infrared Imaging to Evaluate Emotional Competences in Nursing Students: A First Approach through a Case Study

Abstract: During university studies of nursing, it is important to develop emotional skills for their impact on academic performance and the quality of patient care. Thermography is a technology that could be applied during nursing training to evaluate emotional skills. The objective is to evaluate the effect of thermography as the tool for monitoring and improving emotional skills in student nurses through a case study. The student was subjected to different emotions. The stimuli applied were video and music. The proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The average values of temperature and blood perfusion were calculated for every emotion. The ROIs analyzed were the nose, forehead, eyes, upper lip region, and total face evaluation, according to the recommendations of previous works [14], [16], [17]. For the quantitative analysis of the results, the absolute and percentage differences between the negative valence-baseline and positive valence-baseline images for temperature and blood perfusion were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average values of temperature and blood perfusion were calculated for every emotion. The ROIs analyzed were the nose, forehead, eyes, upper lip region, and total face evaluation, according to the recommendations of previous works [14], [16], [17]. For the quantitative analysis of the results, the absolute and percentage differences between the negative valence-baseline and positive valence-baseline images for temperature and blood perfusion were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Previous works [14], [16], [17] have shown that analyzing several points in the face, such as the cheeks, periorbital region, upper lip region, and forehead, can allow one to identify the type of Accepted Version -Journal of Thermal Biology, december 2022. The publisher version can be found with the DOI: 10.1016/j.jtherbio.2023.103464 emotion defined in the modular approach by analyzing if there is an increase or decrease in temperature in those regions.…”
Section: Introductionmentioning
confidence: 99%
“…The International Vocabulary of Metrology (VIM) [40], defines the systematic measurement error as the part of the measurement error that remains constant or varies predictably A specific workflow is used to display the results, which converts the thermograms into 3D viewable models, but with a unique feature: the third axis does not actually represent the elevation, depth, or any metric value, but the temperature of the object surface [41]. This method has been used with success in the subjects of health sciences degrees for blood flow monitoring and also for emotions [42].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several computer-based methods have been developed to recognize facial expression through thermograms [25][22] [26][27] [28][29] [30][31] [32]. Previous research shows that feature learning is still performed manually and not specifically designed for the education sector.…”
Section: Introductionmentioning
confidence: 99%